(untitled) (SAARC Journal of Agriculture, 2016)
The study was conducted to identify the present status of integrated farming and its impacts on farmers livelihood in comparison to mixed farming. Following two stages sampling procedure, a total of 420 farmers (210 for integrated farming and 210 for mixed farming) were selected from seven study areas of six districts on the basis of having intervention from different NARS institutes and without having any intervention from any organization. Descriptive statistics like sum, average, percentage, etc. were derived and calculated for analyzing the socioeconomic data. Propensity score matching (PSM) were applied with Kernel matching and Radius matching methods to evaluate the impact of integrated farming on farmers employment creation and income generation. The highest employment duration for male was 152.5 man-days/year for the farming system C-L-P-F-H under integrated farms and for mixed farms, it was 104.5 man-days/year. The average total income of the integrated farms was Tk. 124839 and for mixed farms, it was Tk. 99641. Average calorie intake of food secure households was 2927.83 kcal and 2839.14 kcal for integrated farming and mixed farming which is higher than the national average calorie intake (i.e., 2122 kcal). To assess the livelihood pattern through asset pentagon approach, noteworthy improvement was found based on different capitals of farm households practicing integrated farming in comparison to mixed farming. Finally, based on different problems, a constraint facing index was calculated in order to suggest policy recommendations. SAARC J. Agri., 13(2): 61-79 (2015)